Comparative study of potentially toxic metals (Cu, Al, Cr, Cd, Hg, Ni) and metalloid (As) in liver and muscle tissue; and their influence on the percentage of protein in chicken meat - Rossi Salinas, Gloria María (2025)
The growing number of informal poultry farms does not guarantee that chicken feed is adequate, and it may contain heavy metals or ecotoxic metalloids accumulated in meat and liver. The presence of these elements can adversely influence the protein content of meat (%P), and impact consumer health. Fresh samples of liver and muscle tissue (n = 50 and n = 56, respectively) collected from the main supply centres of the eight (8) provinces of the department of Arequipa, Peru, were analysed to determine Cu, Al, Cr, As, Cd, Hg and Ni, by inductively coupled plasma mass spectrometry (ICP-MS); as well as the %P in muscle tissue by the Kjeldahl method to determine their correlation. The concentration of the elements was higher in liver (h) than in muscle tissue (m), without implying risk for their consumption. The mean and standard error of %P in (m) was 22.12% ± 0.18 and the 95% confidence interval CI = 21.757 - 22.474%, with %P having a moderate, positive and significant correlation at the 0.000 level with the chromium concentration in (m), while the correlation with the chromium concentration in (h) was significant at the 0.05 level and also moderate, positive.